Prevalence of Neonatal Hyperbilirubinemia Based on Mother's and Infant's Blood Group in Cengkareng Hospital - Andhika Tiurmaida Hutapea; Suryadi Susanto; Novita Anggraeni; Gracela Salurante (Jurnal MedScientiae, 2023)
Hyperbilirubinemia is an increase in bilirubin levels >5 mg/dL which is characterized by the appearance of pathological jaundice. In the 2017 SKDI, the neonatal mortality rate was 19 per 1000 live births. The purpose of this study was to find out the prevalence of neonatal hyperbilirubinemia based on the blood group of the mother and the baby at Cengkareng General Hospital for the period January to March 2023. This research was conducted from January to March 2023 with an observational descriptive nature. This research was conducted at Cengkareng Hospital, West Jakarta. The study concluded that ABO incompatibility is not the only factor that contributes to hyperbilirubinemia in neonates. The results showed that 15 (41.7%) babies with hyperbilirubinemia came from mothers with blood type O, while the majority of babies who experienced hyperbilirubinemia were babies with blood type O, namely 16 (44.4%) babies. The majority of infants who experienced hyperbilirubinemia occurred in infants with blood group O and mothers with blood type O, namely 11 (30.6%), followed by infants with blood group A and mothers with blood type A, namely 4 (11.1%).